“educating children for wisdom”: reflecting on the philosophy for children community of inquiry approach through plato’s allegory of the cave - abarejo, cathlyne (childhood & philosophy, 2024)
There is a widespread belief in Philosophy for Children that Plato, the famed Greek thinker who introduced philosophizing to the world as a form of dialogue, was averse to teaching philosophy to young children. Decades of the implementation of P4C program’s inquiry pedagogy have shown conclusively that children are not, in fact, incapable of receiving philosophical training and education. But was Plato wrong? Or has he been largely misunderstood? Does his theory of education show the value of cultivating virtues in the young? This paper attempts to answer these questions by reading the Republic, specifically Plato’s theory of education and the allegory of the cave, as an education manual that can strengthen one’s understanding of the pedagogical approach of P4C and the importance of educating children in wisdom and other intellectual virtues. It demonstrates that the Platonic conception of education is consistent with P4C’s theoretical position of education being transformative, facilitative, and virtue-based. By unpacking the symbolisms and meanings of the cave metaphor, it also discusses effective facilitation, teacher capacity building, and sharing of responsibility in education. Ultimately, drawing from Plato’s theory of education can recalibrate and improve the way one sees the role of education in building caring communities that empower learners and educators for democracy, higher learning, and achievement.